2021
DOI: 10.3727/096504021x16214197880808
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of MGMT Gene Methylation in Neuroendocrine Neoplasms

Abstract: Unresectable neuroendocrine neoplasms (NENs) often poorly respond to standard therapeutic approaches. Alkylating agents, in particular temozolomide, commonly used to treat high-grade brain tumors including glioblastomas, have recently been tested in advanced or metastatic NENs, where they showed promising response rates. In glioblastomas, prediction of response to temozolomide is based on the assessment of the methylation status of the MGMT gene, as its product, O-6-methylguanine-DNA methyltransferase, may cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…In accordance with the frequent CNV alterations described in primary intracranial sarcomas, DICER1-mutant [6], and with the observed high Ki67 index (Figure 3), we found, in both cancer lesions, 1q and 9p chromosome deletions and high amplification of the CCND2 gene encoding for the D2-type cyclin protein, a strong regulator of cell cycle onset and, thus, of proliferation (Figure 4A). MGMT promoter methylation analysis by Methylation Specific PCR (MSP) [12] showed that the MGMT promoter was not methylated.…”
Section: Classification Based On Dna Methylation Profilingmentioning
confidence: 99%
“…In accordance with the frequent CNV alterations described in primary intracranial sarcomas, DICER1-mutant [6], and with the observed high Ki67 index (Figure 3), we found, in both cancer lesions, 1q and 9p chromosome deletions and high amplification of the CCND2 gene encoding for the D2-type cyclin protein, a strong regulator of cell cycle onset and, thus, of proliferation (Figure 4A). MGMT promoter methylation analysis by Methylation Specific PCR (MSP) [12] showed that the MGMT promoter was not methylated.…”
Section: Classification Based On Dna Methylation Profilingmentioning
confidence: 99%
“…MSP can rapidly assess the methylation status of any CpG site within a CpG island [22,23]. In a first step, DNA is treated with sodium bisulfite, resulting in the conversion of unmethylated cytosine into uracil while the methylated cytosine, resistant to bisulfite, remains unaltered.…”
Section: Techniques For Mgmt Methylation Assessment In Glioblastomasmentioning
confidence: 99%
“…Methylation of O6‐methylguanine‐DNA methyltransferase (MGMT) has been extensively investigated as a biomarker for prediction of pharmacological response to temozolomide in patients affected by GBM 21,22 . MGMT gene is located on chromosome 10q26.3 23‐25 . The expression of MGMT gene is mainly regulated by epigenetic mechanisms.…”
Section: Mgmtmentioning
confidence: 99%
“…To evaluate the methylation status of target genes, it is possible to also perform Amplicon Bisulfite sequencing (ABS) based on NGS technology 94 . This technique allows one to study the methylation status of a target gene with high sequencing depth, but, also in this case, the costs of the technology are quite high and thus not routinely used in clinical practice 25 …”
Section: Technical Approaches To Investigate Epigenetic Biomarkers In...mentioning
confidence: 99%